IMPLEMENTASI GOOD CORPORATE GOVERNANCE PADA PT. PENERBIT ERLANGGA CABANG SURABAYA - DAWAM, AULIA (Jurnal Akuntansi AKUNESA, 2013)
This research aims to find out implementations of GCG (Good Corporate Governance) in thecompany of PT. Penerbit Erlangga, thebranch of Surabaya. TheMethod of data collection inthese studies uses questionnaires and GCG uses likert scaleto measure the level ofimplementation. The results of this research show the implementation of Good CorporateGovernance in this company does not reveal the financial information clearly and it can not beaccessed by interested parties easily or lack of transparency.However,PT Penerbit Erlanggakeepsapplying Good Corporate Governance principles well.Keywords: GCG (Good Corporate Governance)